2021
DOI: 10.1001/jamanetworkopen.2021.35765
|View full text |Cite
|
Sign up to set email alerts
|

Misleading Reporting (Spin) in Noninferiority Randomized Clinical Trials in Oncology With Statistically Not Significant Results

Abstract: Key Points Question Is the interpretation and reporting of noninferiority trials with primary end point results that are not statistically significant correct, and what are the associated factors of misleading reporting? Findings This systematic review of 52 noninferiority randomized clinical trials of cancer treatments with results for primary end points that are not statistically significant, 75% included misleading reporting. Multivariable analysis found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 89 publications
1
21
1
Order By: Relevance
“…This misleading reporting in clinical trials has been termed “spin.” 10 A recent systematic review of oncologic noninferiority clinical trials that did not meet statistical significance for noninferiority showed that 75% had spin. 11 Compared with a previous review of spin, the authors reported the prevalence of spin in noninferiority clinical trials was higher than superiority clinical trials. Spin strategies included emphasizing trends for primary endpoints, conclusions based on secondary endpoints, or conclusions based on subgroup analyses.…”
Section: Discussionmentioning
confidence: 83%
“…This misleading reporting in clinical trials has been termed “spin.” 10 A recent systematic review of oncologic noninferiority clinical trials that did not meet statistical significance for noninferiority showed that 75% had spin. 11 Compared with a previous review of spin, the authors reported the prevalence of spin in noninferiority clinical trials was higher than superiority clinical trials. Spin strategies included emphasizing trends for primary endpoints, conclusions based on secondary endpoints, or conclusions based on subgroup analyses.…”
Section: Discussionmentioning
confidence: 83%
“…Our findings also underscore that all RCTs comparing BCT and TM outcomes were not originally designed to test equivalence or non-inferiority between BCT and TM. It is not ideal to use such RCT findings to establish noninferiority [23,24]. Logistically, not being able to reject the hypothesis that BCT is the same as TM in OS (as designed in a superiority trial) does not provide the desired evidence to establish equivalence of the two arms with pre-defined type I and type II error rates.…”
Section: Discussionmentioning
confidence: 99%
“…In a scoping review of comparisons between abstracts and full reports in primary biomedical research, Li et al 25 found that the level of consistency ranged from 55% to 95%, which included consistency in designating a primary outcome measure 25. On a related note, some studies looked at the prevalence of spin in the medical literature and a systematic review found that 75% of non-inferiority oncology trials had evidence of misleading reporting (spin) 26. Another study identified spin in 34.5% of abstracts of systematic reviews and meta-analyses in emergency medicine 27.…”
Section: Discussionmentioning
confidence: 99%